What is SAPS 'doing' in Kinshasa? Exploring the dyamics of South-South policing building - Van der Spuy, Elrena (2016)
On the surface, South Africa seems well positioned to play a leading role in development cooperation in Africa. Support for such a role is appealing at a time when the notion of South-South exchanges is current. Beyond the political rhetoric, however, there lie a range of issues which at present hamper the role of South Africa, and its public police agency, the South African Police Service, in particular. These issues are explored through an examination of South African Police Service's assistance to the Police Nationale Congolaise (hereinafter referred to as the PNC) in the Democratic Republic of Congo (hereinafter referred to as the DRC). For purposes of this enquiry I rely on a field visit to Kinshasa and a series of interviews with South African Police Services' (hereinafter referred to as SAPS) officials conversant with the emerging dynamics of developmental assistance to other police institutions within the region. From this case study - admittedly brief and limited - some broader observations relevant to South-South assistance in the terrain of safety and security are made, in the hope of helping advance our understanding of the role of the police in police building during state reconstruction